2014
DOI: 10.1021/ac500803w
|View full text |Cite
|
Sign up to set email alerts
|

Protein Molecular Data from Ancient (>1 million years old) Fossil Material: Pitfalls, Possibilities and Grand Challenges

Abstract: Advances in resolution and sensitivity of analytical techniques have provided novel applications, including the analyses of fossil material. However, the recovery of original proteinaceous components from very old fossil samples (defined as >1 million years (1 Ma) from previously named limits in the literature) is far from trivial. Here, we discuss the challenges to recovery of proteinaceous components from fossils, and the need for new sample preparation techniques, analytical methods, and bioinformatics to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 109 publications
0
19
0
Order By: Relevance
“…This may be counterproductive in studies targeting NCPs of extinct taxa. Collagen I is the most abundant protein in bone tissue, but it contains minimal informative sequence variation between species; therefore, improving access to NCPs in the bone proteomes of extinct taxa may significantly increase our access to phylogenetically relevant data (Cleland, Voegele & Schweitzer, 2012; Schweitzer, Schroeter & Goshe, 2014; Wadsworth & Buckley, 2014). However, studies targeting NCPs in ancient bone that discard, or simply do not analyze, the demineralization fraction and subsequent water “washes” may be discarding the NCPs they seek.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be counterproductive in studies targeting NCPs of extinct taxa. Collagen I is the most abundant protein in bone tissue, but it contains minimal informative sequence variation between species; therefore, improving access to NCPs in the bone proteomes of extinct taxa may significantly increase our access to phylogenetically relevant data (Cleland, Voegele & Schweitzer, 2012; Schweitzer, Schroeter & Goshe, 2014; Wadsworth & Buckley, 2014). However, studies targeting NCPs in ancient bone that discard, or simply do not analyze, the demineralization fraction and subsequent water “washes” may be discarding the NCPs they seek.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, molecular sequences recovered from fossils have the potential to shed light on the origin of evolutionary novelties (e.g., feathers), resolve evolutionary relationships (e.g., Buckley, 2015; Welker et al, 2015), and identify indeterminate or fragmentary fossil elements to the taxon that produced them (Buckley et al, 2010). However, until recently, molecular data were thought to be inaccessible from fossil remains, particularly those older than one million years (Schweitzer, Schroeter & Goshe, 2014 and references therein). Proteomic analyses of archeological and paleontological bone tissues are fraught with many challenges that hinder the widespread application of these techniques to fossils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards the end of our original publication on compareMS2, we suggested that "the applicability of the method to other types of samples, such as animal hair, skin, fresh or fossilized bone, remains to be investigated". In analysis of old (centuries or more) bone material in other studies, highly modified (hydroxyproline) collagen peptides were primarily identified . This is obviously a challenge for compareMS2, although a 200‐year‐old pig bone was still identifiable as porcine by compareMS2 (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…Knowledge of protein sequence can, for example, be used to infer evolutionary relatedness between organisms and using protein sidesteps contamination issues that may be problematic when recovered DNA samples are amplified. The virtues and challenges of ancient protein recovery are numerous [44], but evidence of the potential of proteins to be preserved for extreme lengths of time has been shown in work where peptide sequences were extracted from ostrich shells dated to be 3.8 m years old [45], and sequences of collagen have been recovered from 3.4 m years old camel bones, allowing comparison with other ancient and existing species [46]. Even partial sequences of bone matrix and vessel proteins from 60 to 80 m years old dinosaur specimens have been reported [5], [47], [48], [49], [50] and while, the validity of the results has been questioned [45], recently, some of them have been reproduced using an independent experimental procedure [51].…”
Section: Molecular Palaeontologymentioning
confidence: 99%